2012
DOI: 10.1186/1748-717x-7-119
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of brain metastases in completely resected pathological stage IIIA-N2 non-small cell lung cancer

Abstract: BackgroundBrain metastases (BM) is one of the most common failures of locally advanced non-small cell lung cancer (LA-NSCLC) after combined-modality therapy. The outcome of trials on prophylactic cranial irradiation (PCI) has prompted us to identify the highest-risk subset most likely to benefit from PCI. Focusing on patients with completely resected pathological stage IIIA-N2 (pIIIA-N2) NSCLC, we aimed to assess risk factors of BM and to define the highest-risk subset.MethodsBetween 2003 and 2005, the records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 41 publications
3
29
2
Order By: Relevance
“…The HR of 0.36 found for brain metastases reduction in the bevacizumab arms in nsNSCLC in the current study had little overall benefit for the study population analyzed (17), but that might change for nsNCLC patients at high risk to develop brain metastases: in locally advanced (particularly stage IIIA) nsNSCLC, brain metastases occur in 40% to 50% of patients within 2 years after diagnosis (3)(4)(5), many of them as site of first relapse. Similarly, a recent retrospective analysis of noncontrolled data of a smaller number of advanced NSCLC patients (n ¼ 159) implicated less Bevacizumab prolongs survival in a mouse model of nsNSCLC brain metastasis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The HR of 0.36 found for brain metastases reduction in the bevacizumab arms in nsNSCLC in the current study had little overall benefit for the study population analyzed (17), but that might change for nsNCLC patients at high risk to develop brain metastases: in locally advanced (particularly stage IIIA) nsNSCLC, brain metastases occur in 40% to 50% of patients within 2 years after diagnosis (3)(4)(5), many of them as site of first relapse. Similarly, a recent retrospective analysis of noncontrolled data of a smaller number of advanced NSCLC patients (n ¼ 159) implicated less Bevacizumab prolongs survival in a mouse model of nsNSCLC brain metastasis.…”
Section: Discussionmentioning
confidence: 93%
“…Lung cancer is responsible for about 60% of all brain metastases (2). In patients with locally advanced (stage III) nsNSCLC without any residual disease after initial treatment, the incidence of brain metastases is particularly high, ranging from 44% to 63% (3)(4)(5). Brain metastases contribute to the bad outcome of these patients, with 5-year survival rates below 20% (6).…”
Section: Introductionmentioning
confidence: 99%
“…Although knowledge regarding modifiable risk factors is scarce, several nonmodifiable risk factors are known to influence the cumulative incidence of brain metastasis. Brain metastasis are more common in younger cancer patients than older cancer patients in breast cancer and melanoma [8,9,153,185,[187][188][189][190][191][192][193][194]. The risk of brain metastasis appears to increase until 40 to 49 years of age and then decline thereafter [131].…”
Section: Risk Factorsmentioning
confidence: 99%
“…A study conducted by Vuong et al [196] found males had a higher prevalence of brain metastasis than females (p<0.001), but the frequency of brain metastasis in a study conducted by Pickren et al [131] was not different (8.8% in men and 8.7% in women). Race has not been associated with brain metastasis [131] and was not included as a covariate in the majority of studies [8,9,185,187,[189][190][191][192][193][194][195][197][198][199][200][201][202][203][204]. Breast cancer is the most common source of brain metastasis for women [5].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Among the studies, four (Wang et al, 2009;Horinouchi et al, 2012;Ding et al, 2012;Lee et al, 2012) recruited participants from Asia, four (Robnett et al, 2001;Mamon et al, 2005;Arrieta et al, 2009;Hubbs et al, 2010) recruited participants from North America, and five (Ceresoli et al, 2002;Keith et al, 2002;Bajard et al, 2004;Petrović et al, 2011;Dimitropoulos et al, 2011) recruited participants from Europe. In addition, 11 studies involved retrospective analyses and 2 studies (Arrieta et al, 2009;Dimitropoulos et al, 2011) involved prospective analyses.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%